Knowledge on essential newborn care among antenatal mothers attending tertiary care hospital - J., Aravindan; N. C., Indira; A., Mithun Kumar (International Journal Of Community Medicine And Public Health, 2021)
Background: Globally 4 million newborn die every year before they reach the age of one month. To achieve the millennium developmental goals newborn survival is essential. Aim of the study was to assess the level of knowledge of antenatal women on essential new born care and danger signs during neonatal period, to find the association of sociodemographic and obstetric characteristics with maternal knowledge level. Settings and design included descriptive cross-sectional study was conducted in a tertiary care hospital. Methods: The study enrolled 439 antenatal women by convenient sampling technique. A pretested semi structured questionnaire was used to assess the knowledge. Statistical package for the social sciences (SPSS) 21 version was used to analysis the data. Chi square was calculated to find the association. P value of <0.05 was considered statistically significant. Results: The study shows that 16.7% respondents had adequate knowledge about danger signs during neonatal period. The maternal age, parity, socioeconomic status, parity had significantly associated with the maternal knowledge regarding new-born care (p<0.05). Conclusions: Majority of the ante natal mother had poor knowledge on new born care.